The Subtitling Of Humour In Deadpool: A Reception Study - Iliya Nurul Iman Mohd Ridzuan, Mohamad Zakuan Tuan Ibharim, Mohamad Faizal Abd Matalib, (Opción, 2019)
This study sought to examine the reception of subtitled humour via the audience‟s outlook. The translation of Deadpool as broadcasted by ASTRO GO was selected as the corpus. The data elicitation procedures involved the screening of selected video clips of the corpus, and subsequently, the respondents were asked to fill out a questionnaire. The results showed an array of the audience‟s understanding and evaluation of the (incorporation) of different types of humour. The audience‟s levels of general knowledge, English proficiency and also comic reference were encompassed as the main factors underlying the understanding of the reception